Elastic, double-layered poly (l-lactide-co-E-caprolactone) scaffold for long-term vascular reconstruction - Mun, Cho Hay; Kim, Sang-Hoon; Jung, Youngmee; Kim, Sang-Heon; Kim, Ae-kyeong; Kim, Dong-Ik; Kim, Soo Hyun (SAGE PUBLICATIONS LTD, 2013)
Synthetic vessel grafts have been used as vascular substitutes for cardiovascular bypass procedures. In this study, we developed a novel tubular double-layered poly(l-lactide-co-E-caprolactone) scaffold that did not require pretreatment with cell seeding by promoting autologous tissue regeneration by inducing the proliferation and differentiation of endothelial and smooth muscle progenitor cells after implantation. The patency and mechanical properties were maintained for one year after implantation, although 95% of the poly(l-lactide-co-E-caprolactone) scaffolds had degraded. After this period, there was a lining of endothelial cells, an accumulation of collagen and elastin, and the development of neovascularization inside the poly(l-lactide-co-E-caprolactone).
Keywords: IN-VIVO; ENDOTHELIAL-CELLS; GRAFT; BIOMATERIALS; REGENERATION; FABRICATION; COPOLYMER; EVENTS; GROWTH